2011
DOI: 10.1002/cbic.201000644
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Functionalized DNA Containing 5‐Modified Pyrimidines by Type II Restriction Endonucleases

Abstract: A series of six pyrimidine-modified dNTPs--5-ethynyl-, 5-phenyl-, and 5-(3-nitrophenyl)deoxycitidine and -deoxyuridine triphosphates--were prepared and incorporated by primer extension with Vent (exo-)polymerase to specific DNA sequences within or next to the recognition sequences of selected restriction endonucleases. The cleavage of these pyrimidine-modified DNA sequences by 13 restriction enzymes was then studied. Whereas the presence of any modified C within the target sequence completely prevented any res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…Nucleophilic substitution with sodium azide [34] followed by reactionw ith 2-chloroethanesulfonyl chloride affordedt he desired compound 3 in acceptabley ield (34 %o vert wo steps). [36,37] Therefore, the study required the preparation of 2'-deoxycytidine triphosphates that contained an alkyne moiety at position 5( dC E TP and dC O TP)a ss ubstrates for the polymerase synthesis of alkyne-modified DNA. [36,37] Therefore, the study required the preparation of 2'-deoxycytidine triphosphates that contained an alkyne moiety at position 5( dC E TP and dC O TP)a ss ubstrates for the polymerase synthesis of alkyne-modified DNA.…”
Section: Resultsmentioning
confidence: 89%
“…Nucleophilic substitution with sodium azide [34] followed by reactionw ith 2-chloroethanesulfonyl chloride affordedt he desired compound 3 in acceptabley ield (34 %o vert wo steps). [36,37] Therefore, the study required the preparation of 2'-deoxycytidine triphosphates that contained an alkyne moiety at position 5( dC E TP and dC O TP)a ss ubstrates for the polymerase synthesis of alkyne-modified DNA. [36,37] Therefore, the study required the preparation of 2'-deoxycytidine triphosphates that contained an alkyne moiety at position 5( dC E TP and dC O TP)a ss ubstrates for the polymerase synthesis of alkyne-modified DNA.…”
Section: Resultsmentioning
confidence: 89%
“…On the other hand, some less bulky modificationsa re often tolerated at position7 of 7-deazaadenine and at position 5o fu racil. [14][15][16] This might indicatet hat, at least for some REs, the major-grooves pecific recognition of the G:Cp airs might be more important than that of A:Tp airs. However,b ecause even the enzymes that tolerate modifications on Aa nd T do not cleave the sequences with A:Tt oT :A mutation, they still must have other means for the recognitiono fA:T pairs that are not affected by small majorgroove substituents.…”
Section: Study Of the Influence Of Modified Guaniner Esidues Within Rmentioning
confidence: 96%
“…The residue was co-evaporated several times with water.T he product was purified by HPLC chromatography [aq. TEAB ( (100) (16,dG Ac TP):N ucleoside 14 (53 mg, 0.146 mmol) was suspended in trimethyl phosphate (426 mL) in an argonpurged vial, and the suspension was cooled to 0 8C. Then, non-redistilled POCl 3 (20 mL, 0.215 mmol) was added.…”
Section: -Amino-5-methyl-37-dihydro-7-[2-deoxy-b-d-erythro-pentofurmentioning
confidence: 99%
“…The incorporation of 7-deazaA was used [3] as a means of permanently protecting DNA against cleavage by certain REs. Recently, we reported a systematic study of the cleavage of DNA containing 7-substituted 7-deazaadenines [4] and 5-substituted pyrimidines; [5] we found a surprising tolerance of several REs to the presence of not only 7-deazaadenine but also some 7-substituted derivatives. In these studies, [4,5] permanent protection against cleavage by REs was also demonstrated.…”
mentioning
confidence: 97%